Association between Adherence to Guideline-Recommended Preventive Medications and In-Hospital Mortality among Non-Reperfused ST-Elevation Myocardial Infarction Patients Admitted to a Tertiary Care Academic Center in a Developing Country. Issue 1 (6th February 2020) - Irawati, Sylvi; Dharma, Surya; Taxis, Katja; Nguyen, Thang; Nursyarofah, Nunung; Wilffert, Bob; Hak, Eelko
Background and aims: Acute ST-elevation myocardial infarction (STEMI) is a potentially fatal presentation of coronary artery disease (CAD). Evidence of the impact of acute pharmacological interventions in non-reperfused STEMI patients on subsequent events is limited. We aimed to assess the association between adherence to guideline-recommended preventive medications and in-hospital mortality among this high-risk patient population. Methods: We conducted a cohort study using data obtained from the Jakarta Acute Coronary Syndrome (JAC) Registry database from a tertiary care academic hospital in Indonesia. We included 1132 of 2694 patients with STEMI recorded between 1 January 2014 and 31 December 2016 who did not undergo acute reperfusion therapy. Adherence to guideline-recommended preventive medications was defined as the combined administration of aspirin, clopidogrel, anticoagulants and statins after hospital admission. The main outcome measure was in-hospital mortality. Results: Overall, 778 of 1132 patients (69%) received the combination of preventive medications. The guideline non-adherent group had significantly more patients with earlier onset of STEMI, higher Killip class and thrombolysis in myocardial infarction (TIMI) score. After adjustments for measured characteristics using logistic regression modeling, exposure to the combination of preventive therapies was associated with a statistically significant lower risk for in-hospital mortality (adjusted odds ratio: 0.46, 95% confidence interval: 0.30–0.70). Conclusions: Adherence to guideline-recommended preventive medications was associated with lower risk of in-hospital mortality in non-reperfused STEMI patients. The predictors of not receiving these medications need to be confirmed in future research.